2022
DOI: 10.1002/etc.5361
|View full text |Cite
|
Sign up to set email alerts
|

Anticoagulant Rodenticide Contamination of Terrestrial Birds of Prey from Western Canada: Patterns and Trends, 1988–2018

Abstract: As the dominant means for control of pest rodent populations globally, anticoagulant rodenticides (ARs), particularly the second‐generation compounds (SGARs), have widely contaminated nontarget organisms. We present data on hepatic residues of ARs in 741 raptorial birds found dead or brought into rehabilitation centers in British Columbia, Canada, over a 30‐year period from 1988 to 2018. Exposure varied by species, by proximity to residential areas, and over time, with at least one SGAR residue detected in 74%… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 19 publications
(18 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…Indeed, the Convention on the Conservation of Migratory Species of Wild Animals (the CMS, or Bonn Convention) highlighted secondary exposure to ARs as one of the most important toxicological hazards for migratory birds (CMS, 2014). The high acute toxicity and persistence of ARs in animal tissues, especially of SGARs, has led to their becoming ubiquitous in rodent-predator-scavenger food webs (López-Perea and Mateo, 2018;Pay et al, 2021;Elliott et al, 2022;Cooke et al, 2022). Baits containing ARs may be consumed by a number of non-target primary consumers (e. g., invertebrates, fish, wild birds and mammals), increasing the risk of exposure across the entire food web (Shore and Coeurdassier, 2018;Regnery et al, 2020;Alabau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, the Convention on the Conservation of Migratory Species of Wild Animals (the CMS, or Bonn Convention) highlighted secondary exposure to ARs as one of the most important toxicological hazards for migratory birds (CMS, 2014). The high acute toxicity and persistence of ARs in animal tissues, especially of SGARs, has led to their becoming ubiquitous in rodent-predator-scavenger food webs (López-Perea and Mateo, 2018;Pay et al, 2021;Elliott et al, 2022;Cooke et al, 2022). Baits containing ARs may be consumed by a number of non-target primary consumers (e. g., invertebrates, fish, wild birds and mammals), increasing the risk of exposure across the entire food web (Shore and Coeurdassier, 2018;Regnery et al, 2020;Alabau et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Predator species that are highly specialized rodent-feeders, such as snakes, kestrels, owls and mustelids, are at a high risk of SGAR exposure (Lettoof et al, 2020;Roos et al, 2021;Elliott et al, 2022). However, generalist predators and scavengers may be exposed to secondary SGAR poisoning at similar or even higher levels than specialist predators (López-Perea and Mateo, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…In the United States, although the accessibility of SGARs to nonprofessional applicators is not allowed since the middle of the 2010s, the prevalence of brodifacoum in red-tailed hawks remained almost 100%, and the others increased . In contrast, an increase in brodifacoum and a decrease in bromadiolone in terrestrial raptors were reported in Western Canada after the regulation measures restricting outdoor use of brodifacoum . In the last case, only bromadiolone was permitted for outdoor use by licensed operators, which might lead a switch in sales of bromadiolone and brodifacoum .…”
Section: Discussionmentioning
confidence: 99%
“…Small rodents cause widespread conflict with human interests by transmitting disease and costly damage to crops, food stores, and infrastructure. Anticoagulant rodenticides (ARs) are widely used to control rodent populations to reduce these consequential impacts . However, the use of ARs has resulted in secondary exposure of various animals, including birds of prey. Exposure of predatory birds to ARs is likely to include feeding on either or both rodenticide “target” and “nontarget” small mammals. , Target rodents in the United Kingdom (UK) are typically the brown rat Rattus norvegicus and the house mouse Mus musculus, while nontarget rodents are primarily wood mouse Apodemus sylvaticus and bank vole Myodes glareolus. , As rats and mice with resistance to the first-generation AR appeared, more toxic second-generation anticoagulant rodenticides (SGARs) were developed and used, , which has resulted in worldwide exposure of wildlife to SGARs and poisoned cases.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, the use of rodenticides can have very negative effects on biodiversity (Moriceau et al, 2022; Nakayama et al, 2018; Rattner et al, 2014; Singleton et al, 2007). Rodenticides do not only affect species of birds, mammals, and reptiles that feed on rodents (Elliott et al, 2022; Fernandez‐de‐Simon et al, 2022; Lettoof et al, 2020; Lohr, 2018; Roos et al, 2021; Ruiz‐Suárez et al, 2014; Serieys et al, 2015), they can also affect other species (Oliva‐Vidal et al, 2022; Stone et al, 1999; Vyas, 2017). Furthermore, the most widely used rodenticides are known to inflict extremely painful and slow deaths to rodents (Baker et al, 2022; Mason & Littin, 2003).…”
Section: The Role Of Cats In Rodent Managementmentioning
confidence: 99%